3-w-(7w+12)=2(w-3)

Simple and best practice solution for 3-w-(7w+12)=2(w-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-w-(7w+12)=2(w-3) equation:


Simplifying
3 + -1w + -1(7w + 12) = 2(w + -3)

Reorder the terms:
3 + -1w + -1(12 + 7w) = 2(w + -3)
3 + -1w + (12 * -1 + 7w * -1) = 2(w + -3)
3 + -1w + (-12 + -7w) = 2(w + -3)

Reorder the terms:
3 + -12 + -1w + -7w = 2(w + -3)

Combine like terms: 3 + -12 = -9
-9 + -1w + -7w = 2(w + -3)

Combine like terms: -1w + -7w = -8w
-9 + -8w = 2(w + -3)

Reorder the terms:
-9 + -8w = 2(-3 + w)
-9 + -8w = (-3 * 2 + w * 2)
-9 + -8w = (-6 + 2w)

Solving
-9 + -8w = -6 + 2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-2w' to each side of the equation.
-9 + -8w + -2w = -6 + 2w + -2w

Combine like terms: -8w + -2w = -10w
-9 + -10w = -6 + 2w + -2w

Combine like terms: 2w + -2w = 0
-9 + -10w = -6 + 0
-9 + -10w = -6

Add '9' to each side of the equation.
-9 + 9 + -10w = -6 + 9

Combine like terms: -9 + 9 = 0
0 + -10w = -6 + 9
-10w = -6 + 9

Combine like terms: -6 + 9 = 3
-10w = 3

Divide each side by '-10'.
w = -0.3

Simplifying
w = -0.3

See similar equations:

| 4x=6z+76 | | 7*7-(8-2)= | | 6+4x=4x-5 | | 2(-x)-4+4x=x+5 | | 13+3x=5x-5 | | 9x+4x=2x+3 | | 13-(4-k)=5k+10-7 | | 37-X=14 | | 48-6x=4x-2 | | 8-g= | | X+150=.75(x+150) | | 3(4x-9)+12=9 | | 5t-7=5t | | 2a+14=-2(-a-3) | | -m-9=15 | | -I-17I= | | 3d-15=3(5+d) | | 11x+2x-9=24 | | 3(4x-9)12=9 | | -2(2a-7)=14-4a | | 3x+8x=9 | | 4x^2+25=7 | | 4a+45+4a+45=31a-2 | | 2x+6+5x=20 | | -7+2x+3=3x+5+2x | | -3+b(x+4)=47 | | 3p-p-5p=-3p-6 | | 7y-6x=72 | | 10+2b=76.50 | | -3(y-2)=6-3y | | 9x-6x+4=-20 | | Y=4cos(6x) |

Equations solver categories